2014
DOI: 10.1042/bj20131110
|View full text |Cite
|
Sign up to set email alerts
|

Sequestration of the abrin A chain to the nucleus by BASP1 increases the resistance of cells to abrin toxicity

Abstract: Abrin, a type II ribosome-inactivating protein, comprises A and B subunits wherein the A subunit harbours toxin activity and the B subunit has a galactose-specific lectin activity. The entry of the protein inside the cell is through the binding of the B chain to cell surface glycoproteins followed by receptor-mediated endocytosis and retrograde transport. A previous study from our laboratory showed that different cell lines exhibited differences of as great as ~200-fold in abrin toxicity, prompting the present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…An earlier study had shown that abrin A chain gets sequestered into the nucleus in KB cells , therefore, we wanted to check whether abrin induces direct DNA damage in these cells. We examined phosphorylation of the Histone 2A family protein member gamma‐H2AX (γH2AX), a marker for double strand breaks in DNA .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…An earlier study had shown that abrin A chain gets sequestered into the nucleus in KB cells , therefore, we wanted to check whether abrin induces direct DNA damage in these cells. We examined phosphorylation of the Histone 2A family protein member gamma‐H2AX (γH2AX), a marker for double strand breaks in DNA .…”
Section: Resultsmentioning
confidence: 99%
“…Till now, there are no reports on direct DNA damage caused by abrin. However, earlier study showing the nuclear sequestration of the A chain in KB cells by BASP‐1 protein led us to examine the effect of ABA in the nucleus, to determine any possible DNA damage caused by the toxin. Our study revealed that abrin caused DNA damage partially independent of caspases in KB, while in Ovcar‐3 cells, abrin‐induced DNA damage was caspase‐dependent, leading to the conclusion that the DNA damage observed in case of KB cells may be also because of direct DNA damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations